Biliary cancer: Utility of next‐generation sequencing for clinical management. Issue 24 (13th September 2016) - Javle, Milind; Bekaii‐Saab, Tanios; Jain, Apurva; Wang, Ying; Kelley, Robin Katie; Wang, Kai; Kang, Hyunseon C.; Catenacci, Daniel; Ali, Siraj; Krishnan, Sunil; Ahn, Daniel; Bocobo, Andrea Grace; et al.
Abstract : BACKGROUND: Biliary tract cancers (BTCs) typically present at an advanced stage, and systemic chemotherapy is often of limited benefit. METHODS: Hybrid capture–based comprehensive genomic profiling (CGP) was performed for 412 intrahepatic cholangiocarcinomas (IHCCAs), 57 extrahepatic cholangiocarcinomas (EHCCAs), and 85 gallbladder carcinomas (GBCAs). The mutational profile was correlated with the clinical outcome of standard and experimental therapies for 321 patients. Clinical variables, detected mutations, and administered therapies were correlated with overall survival (OS) in a Cox regression model. RESULTS: The most frequent genetic aberrations (GAs) observed were tumor protein 53 ( TP53 ; 27%), cyclin‐dependent kinase inhibitor 2A/B ( CDKN2A/B ; 27%), KRAS (22%), AT‐rich interactive domain‐containing protein 1A ( ARID1A ; 18%), and isocitrate dehydrogenase 1 ( IDH1 ; 16%) in IHCCA; KRAS (42%), TP53 (40%), CDKN2A/B (17%), and SMAD4 (21%) in EHCCA; and TP53 (59%), CDKN2A/B (19%), ARID1A (13%), and ERBB2 (16%) in GBCA. Fibroblast growth factor receptor ( FGFR ; 11%) and IDH mutations (20%) were mostly limited to IHCCA but appeared to be mutually exclusive. In the IHCCA group, TP53 and KRAS mutations were associated significantly with poor OS, whereas FGFR2 mutations were associated with improved OS ( P  = .001), a younger age at onset, and female sex. IDH1/2 mutations were not prognostic. In a multivariate model, the effects of TP53 and FGFR GAs remained significant ( P  < .05). Patients with FGFR GAs had superior OS with FGFR‐targeted therapy versus standard regimens ( P  = .006). Targeted therapy in IHCCA was associated with a numerical OS improvement ( P  = .07). CONCLUSIONS: This is the largest clinically annotated data set of BTC cases with CGP and indicates the potential of CGP for improving outcomes. CGP should be strongly considered in the management of BTC patients. Cancer 2016;122:3838–3847. © 2016 American Cancer Society. Abstract : This is the largest clinically annotated data set of biliary tract cancer cases with comprehensive genomic profiling, and it indicates the potential of comprehensive genomic profiling to improve outcomes. Comprehensive genomic profiling should be strongly considered in the management of patients with biliary tract cancer.